'Thermodynamic assessment of the Ag-Zr and Cu-Zr binary systems. (December 2016) - Hsiao, Hsien-Ming; Liang, Song-Mao; Schmid-Fetzer, Rainer; Yen, Yee-wen
Abstract: The Ag-Zr and Cu-Zr binary systems are thermodynamically reassessed in this study. Not only phase diagrams, but also thermodynamic properties, such as enthalpy of formation for solids, activity for liquid, and enthalpy of mixing for liquid, are all calculated and compared with available experimental data to assure the accuracy of the assessment. Cu2 Zr and Cu24 Zr13 phases are considered as meta-stable phases, which would not exist in the Cu-Zr equilibrium phase diagram. The artifact of liquid miscibility gap at high temperature is avoided in the presently calculated phase diagrams. Highlights: Reassess the Ag-Zr and Cu-Zr binary systems. The artifact of liquid miscibility gap at high temperature is avoided in the presently calculated phase diagrams. The Ag-Zr system was optimized by considering all available experimental data. The dataset was built in a more acceptable way in the CALPHAD society. Re-optimize the Cu-Zr system in accordance with new experimental data by [2010Zho], which was not used in recent assessment work by [2011Gie]. Cu2 Zr and Cu24 Zr13 phases are considered as meta-stable phases. The mixing enthalpy of liquid phase is modeled as temperature independence.